Pengaruh Permainan Pasir Dan Permainan Plastisin Terhadap Kreativitas Anak Usia Dini Di Paud Cemerlang Deli Serdang - Ulva Wulandari; Lahmuddin Lubis; Abdul Munir (Universitas Medan Area, 2021)
This study aims to determine the effect of playing sand and plasticine on the creativity of early childhood in CEMERLANG PAUD Deli Serdang. This study used a quantitative descriptive type with quasi experiments design, and used the Time Series Design system. The research subjects were 20 young children aged 5-6 years which were divided into 2 experimental groups, namely experiment I with sand games consisting of 10 students and experiment II with plasticine games. consists of 10 students at CEMERLANG PAUD Deli Serdang. Hypothesis testing is done using the Wiloxon Signed Rank Test.Hypothesis test results show that there is an effect of early childhood creativity before and after playing sand games with an average value (0.00 α = 0.021), there is an effect of early childhood creativity before and after playing plasticine games with an average value (0.00α = 0.022), and there is a difference in the creativity of children playing with sand and plasticine (0.00 α = 0.09). The results showed that there was an effect of playing sand on the creativity of early childhood in CEMERLANG PAUD Deli Serdang with an increase of 21.1%. There is an effect of playing plasticine on the creativity of early childhood in CEMERLANG PAUD Deli Serdang with an increase of 22%. There is a difference in the effect of playing sand and plasticine on the creativity of early childhood in CEMERLANG PAUD Deli Serdang by 0.9%.